2019
DOI: 10.22146/ijbiotech.42750
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and molecular characterization of Anaplasma platys in dog patients in Yogyakarta area, Indonesia

Abstract: Anaplasma platys is a tick-borne, Gram-negative bacterium that causes anaplasmosis, a companion vector-borne disease impacting dogs. Information on this disease remains limited in Indonesia. Its symptoms are not specific, so molecular analysis is required for a rapid and accurate diagnosis. GroEL is an essential gene commonly used for classification and species identification of many groups of bacteria, including Anaplasma spp. In this study, a molecular diagnosis of anaplasmosis based on the groEL gene sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
(35 reference statements)
1
3
0
1
Order By: Relevance
“…E. canis can be detected for a short time in monocytes but cannot be found during the subclinical and chronic stages of infection (Moriera et al 2005). These results of the hematological profile study of dogs infected by E. canis were in line with another previous study conducted by Faizal et al (2019), which used 51 dogs suspected of Anaplasma platys in Yogyakarta, Indonesia.…”
Section: Hematology Profile Of Dog Patients Infected By Ehrlichia Cansupporting
confidence: 90%
“…E. canis can be detected for a short time in monocytes but cannot be found during the subclinical and chronic stages of infection (Moriera et al 2005). These results of the hematological profile study of dogs infected by E. canis were in line with another previous study conducted by Faizal et al (2019), which used 51 dogs suspected of Anaplasma platys in Yogyakarta, Indonesia.…”
Section: Hematology Profile Of Dog Patients Infected By Ehrlichia Cansupporting
confidence: 90%
“…24843/vsmj.2024.v6.i01.p07 Pemeriksaan ulas darah pada anjing kasus, menunjukkan adanya inklusi intracytoplasmic pada eritrosit. intracytoplasmic body merupakan sel inklusi berwarna biru berbentuk bulat, lonjong, atau berbentuk kacang yang memiliki diameter antara 0,35-1,25 μm (Faizal et al, 2019). Ditemukan adanya morula dapat mengindikasikan adanya infeksi anaplasmosis dan ehrlichiosis (Sainz et al, 2015).…”
Section: Pembahasanunclassified
“…Zoonotic TBDs were detected in animals with pathogens such as A. platys, A. marginale, C. burnetti, Borrelia spp., and Rickettsia spp. [175,178,179,181,[183][184][185][186]. Studies on rickettsiosis showed evidence of disease among humans, transmitted by different tick and flea genera [187,188].…”
Section: Indonesiamentioning
confidence: 99%